COLLABORATIVE TEACHING FROM THEORY TO PRACTICE - Galdino Ramos de Oliveira, Edcleison (Revista Gênero e Interdisciplinaridade, 2023)
This article was developed through research where bibliographical references were consulted, from a qualitative point of view, in the area of special education, with emphasis on the contribution of specialized educational services for inclusion students, using the reference of Scientific Work Methodology , by the author Gilberto de Andrade Martins. Aiming to understand how collaborative teaching can help in the teaching-learning process. Evaluate the feasibility of implementing collaborative teaching in Brazilian public schools, taking into account the importance of the school inclusion process. It seeks to dialogue with different experienced contexts and identify different possibilities for a better insertion of children and young people with special needs in the school space, including trying to shed light on the pedagogical practices of special education in general terms. It appears that assessment is a construction and investigation process of the teaching-learning process that leads to the origin of specific functional learning disorders and specialized care for the target audience of special education, involving children, family members, teachers( as), health professionals, pedagogues, management team, among others.